Modelling the associations between students' academic resilience, learning motivation, self-regulated learning and academic well-being in Ghana - Medina Srem-Sai; Francis Arthur; Iddrisu Salifu; Mustapha Amoadu; Paul Obeng; Edmond Kwesi Agormedah; John Elvis Hagan, Jnr.; Thomas Schack (Acta Psychologica)
Introduction: The study explored the associations between academic resilience, learning motivation, self-regulated learning, and academic well-being among students in Ghana. It investigated the direct and mediating roles of learning motivation and self-regulated learning in the relationship between academic resilience and well-being. Methods: A descriptive, cross-sectional survey was conducted among 190 students from three senior high schools in Afram Plains, Ghana. Data were collected using a questionnaire adapted from previous studies, measuring academic well-being, academic resilience, learning motivation, and self-regulated learning. Data were analysed using WebPower online statistical software and SmartPLS version 3 to perform Partial Least Squares Structural Equation Modelling (PLS-SEM). Results: Preliminary analysis indicated non-normality of the data, justifying the use of PLS-SEM. The measurement model showed good psychometric properties and discriminant validity was established between the constructs. The structural model revealed significant direct relationships between academic resilience and well-being, learning motivation, and self-regulated learning. Learning motivation and self-regulated learning were significantly related to academic well-being. Mediation analysis showed that both learning motivation and self-regulated learning partially mediated the relationship between academic resilience and academic well-being. Conclusion: The findings highlight the importance of academic resilience, learning motivation, and self-regulated learning in enhancing academic well-being among the sampled students in Ghana. Designing interventions that strengthen students' resilience through self-regulation principles and motivational tendencies could improve students' academic outcomes and overall well-being.